Evaluating User Acceptance of Sistem Keselamatan in UUM Portal - Siti Nurul Azwani, Abdul Rahman (2005)
User acceptance study has been accepted as one of the important issue in system development since the last few years. This study can be conducted during system development process or after the system has been developed. The most known model for user acceptance is Technology Acceptance Model (TAM). This model has two features; perceived usefulness and perceived ease of use. By using these two features, user acceptance level of Sistem Keselamatan in UUM Portal has been evaluated during this research process. The researcher found that most of the users who have been using Sistem Keselamatan accept Sistem Keselamatan in UUM Portal because of its usefulness and ease of use features. Number of respondents who do not use Sistem Keselamatan is also observed. The reasons why they do not use Sistem Keselamatan is also obtained. From the findings of this study, the researcher is able to give suggestions on how to increase the acceptance level of Sistem Keselamatan. This idea is generated based on the respondents answer on why they do not use Sistem Keselamatan.